A indisciplina e suas representações no cotidiano escolar - Paula, Gisângela Faria de (2005)
The present work aims to investigate, to apprehend and to analyze which the representations of second grade basic education teachers concerning school indiscipline and its implications in school pedagogical practice, and in special, in classroom practice. It also aims to identify the types of intervention adopted by collaborating teachers, as well as by the school, in regard to students’ indiscipline actions. The theoretical base is Social Representations Theory of Moscovici. Through Uberlândia public school second grade groups direct observation, carried through in the fírst semester of 2004, document analysis with registers of school indiscipline occurrences, in the 2003 and 2004, and interviews carried through with the female teachers, the supervisor, the vice-director and director, we verify different forms of indiscipline representation at school environment. The indiscipline, in the context of the investigated school, is represented, mainly, as something tied up with the figure of the student and its familiar education. Others forms of indiscipline representation had been observed: teacher methodological position, lack of school pedagogical support, lack of government support and the presence of a social context that influences child’s behaviors. We observe that the types of intervention adopted by the teachers concerning school context follow two types of action. First, we fmd threats and attitudes such as: verbal rebuke; to leave the student without recreation or sent out of the room, sent to the supervisor. On the other hand, the school adopts an intervention with the helps of the student family. Facing this picture of representations, the search for a formative space that promotes reflexive criticism in the school environment becomes necessary.